Parliamentary Oversight Over the Acts Of Government Under The Palestinian Basic Law Of 2003 - Hamad, Ahmed M A; Mohd Anuar, Haslinda; Halim, Rohizan (Innovare Academics Sciences Pvt. Ltd, 2021)
Parliamentary oversight is the monitoring method over the acts of government in terms of its performance of the authorized powers under the Basic Law of 2003. The objective of this paper is, therefore, to examine the effectiveness of parliamentary oversight over the government's actions. The tools of parliamentary oversight are the right to the inquiry, interrogation, parliamentary investigation, and withdrawal of confidence. This article explains the applicability of the tools in the Palestinian legal system and the effectiveness of these tools in influencing the acts of the government. In order to achieve the objective of this paper, the socio-legal research using the qualitative approach was engaged. This study found that the parliamentary oversight in Palestine was ineffective because of the ambiguity in the law, disruption, and suspension of Parliament, lack of experience on parliamentary customs and the absence of partisan diversity